PENGARUH MATA KULIAH PENGANTAR KEWIRAUSAHAAN DAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN MATEMATIKA - Hamid, Hariaty (Almeera Education, 2025)
This study aims to determine the influence of the Introduction to Entrepreneurship and Entrepreneurship courses on students’ entrepreneurial interest at Universitas Borneo Tarakan. This is a quantitative research using a survey method and multiple linear regression analysis. The sample consisted of 91 students mathematics educations. Data were collected through an entrepreneurial interest questionnaire and students' course grades. The results showed that both courses significantly influenced entrepreneurial interest, both partially and simultaneously. The regression model met all classical assumptions and explained 30.9% of the variation in entrepreneurial interest. These findings emphasize the importance of strengthening entrepreneurship-related courses to foster entrepreneurial motivation among students.